Thrombocytopenia in Plasmodium vivax Malaria - Biswas, Dr. Tapan; Mondal, Dr. Animesh (International Journal of Innovative Research in Medical Science, 2017)
Introduction: Malaria is a disease that affects almost all blood components. Thrombocytopenia is frequently noticed with P. falciparum malaria but is less reported and studied with P. vivax malaria. Materials and Methods: The study was conducted in Infectious Disease & Beliaghata General Hospital, Kolkata -10; West Bengal, India. We included patients who were diagnosed with vivax malaria. The data regarding their clinical and hematological profile was collected and analysed. Result: A total of 60 patients were included. 44 (73.33%) had platelet count <100000/mm3. Mean platelet count was 85,800/cmm, range being 40,000/mm3–2, 10,000/mm3. Conclusion: Thrombocytopenia is now being seen more commonly with vivax malaria. Patients with platelet count <1 lac/cumm have more severe disease.